The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1002/j.1556-6978.1989.tb01109.x
|View full text |Cite
|
Sign up to set email alerts
|

Counseling Self‐Efficacy and Counseling Competence in Prepracticum Training

Abstract: Counseling self‐efficacy and counseling skills were examined over time in a graduate prepracticum class. Efficacy increased with training, but its relationship to performance of skills was weak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0
5

Year Published

1991
1991
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 19 publications
7
56
0
5
Order By: Relevance
“…Johnson et al (1989) reported that students experienced a significant increase in counselor self-efficacy after observing counseling sessions with role-playing graduate students. Larson et aI.…”
Section: Service-learning Educational Outcomes and Counselor Preearmentioning
confidence: 97%
“…Johnson et al (1989) reported that students experienced a significant increase in counselor self-efficacy after observing counseling sessions with role-playing graduate students. Larson et aI.…”
Section: Service-learning Educational Outcomes and Counselor Preearmentioning
confidence: 97%
“…Some of these instruments focus on basic or advanced individual counseling skills (e.g., Johnson, Baker, Kopala, Kiselica, & Thompson, 1989;Larson, Suzuki, Gillespie, Potenza, Bechtel, & Toulouse, 1992), whereas others focus on certain content specialties, such as group counseling, career counseling, school counseling, or psychiatry (e.g., Margolies, Wachtel, & Schmelkin, 1986;O'Brien, Heppner, Flores, & Bikos, 1997;Sutton & Fall, 1995). Although a few items from some of these instruments were designed to assess self-efficacy in the multicultural context, they tend to focus only on parts of the counseling process and assess this construct at intermediate or general levels that may not be helpful in predicting specific outcomes.…”
Section: Problem Statementmentioning
confidence: 99%
“…Most of the existing CSE literature focuses on the relationship between CSE and other important counselor training variables, such as counselor anxiety, counselor performance, and the supervision environment (Johnson et al, 1989;Ridgway & Sharpley, 1990;Sipps, Sugden, & Faiver, 1988). Ten CSE measures were identified by Larson and Daniels (1998).…”
Section: General Cse Measures: Why They Are Not Sufficient For Multicmentioning
confidence: 99%
See 1 more Smart Citation
“…In some of these studies, researchers were interested in investigating relationships between self-efficacy and counselors' level of anxiety, performance, and context of supervision (Johnson, Baker, Kopala, Kiselica, & Thompson 1989;Ridgway & Sharpley, 1990;Sipps, Sugden, & Faiver, 1988). Results of studies conducted on school counselors' self- 2009, 10 (1) 38-42 efficacy revealed that perception of self-efficacy has been seen as an important factor on performance and success of counselors (Larson, Clark, Wesely, Koraleski, Daniels, & Smith, 1999;Tang, Addison, LaSure-Bryant, Norman, O'Connell, & Stewart-Sicking, 2004).…”
Section: Discussionmentioning
confidence: 99%